Pengaruh Implementasi Syariah Governance Terhadap Kepuasan dan Loyalitas Muzakki (Studi pada Lembaga Amil Zakat Se-DIY) - Puspitasari, Radita Dyah; Darma, Emile Satia (Reviu Akuntansi dan Bisnis Indonesia, 2019)
The research aims to examine and obtain empirical study on the effect of syariah governance implementation toward satisfaction and loyalty of muzakki. The object of this research is Amil Zakat Institute in Daerah Istimewa Yogyakarta. Collecting data used purposive sampling method on muzakki who pay zakat through Amil Zakat Institute in Daerah Istimewa Yogyakarta. A total of 215 respondents used as samples in this study. The analysis tool used is structural equation model with AMOS 22.0. Testing the quality of the data used in this research is a confirmatory factor analysis and second order model, while the hypothesis testing used the structural model analysis. The results of  the research showed that syariah governance has a positive significant effect on satisfaction and loyalty of muzakki, while satisfaction is not showing significant effect to the loyalty of muzakki.